Synthesis of Tetrapeptides and Screening of their Antioxidant Properties - Maharani, Rani; Sumiarsa, Dadan; Zainuddin, Achmad; Ammatillah, Nuruzzahra; Hidayat, Ace T.; Harneti, Desi; Nurlelasari; Supratman, Unang (Current Bioactive Compounds, 2019)
Background: Tetrapeptide Pro-Ala-Gly-Tyr (PAGY) is an antioxidant peptide that was isolated by Nikoo et al. (2014) from hydrolysate of skin gelatin of amur sturgeon fish (Acipenser schrenckii). This research aims to synthesize PAGY and its analogues by a solid-phase method, and to screen their antioxidant activities. Methods: PAGY and its analogues, namely, Pro-Ser-Gly-Tyr (PSGY), Pro-Ala-Phe-Tyr (PAFY), Pro- Phe-Phe-Tyr (PFFY) and Pro-Ala-Ile-Tyr (PAIY), were synthesized via a solid phase peptide synthesis method with the Fmoc/t-Bu strategy. The synthesis was undertaken on 2-chlorotritylchloride resin as solid support, and all coupling reactions were facilitated by a combination of HBTU and HOBt reagents. All peptides were cleaved from the resin by using 95% TFA in water. Results: Through the solid-phase synthesis method, all peptides were obtained in 50-85% yields. Pure peptides were analysed by analytical RP-HPLC, and were characterized by HR-TOF-ESI-MS and 1HNMR. DPPH inhibition assay was applied to all of the peptides with IC50 of 1.750; 1.116; 1.177 ;1.437; and 1.642 mg/mL for PAGY, PSGY, PAFY, PFFY, and PAIY, respectively. Conclusion: PAGY and its four analogs were successfully synthesized by solid-phase method. PSGY compound was found to have the highest activity of all in DPPH assay.
Keywords: PAGY